Beyond Cheerleading: eGovernance, Political Communication and Political Behaviour of Nigerian Women - Isola, PhD, Abidemi Abiola; Yacob-Haliso, PhD, Olajumoke; Alao, PhD, Adebukola.A (Covenant University Journal of Politics and International Affairs, 2016)
E-governance, which is the application of Information Communication Technology (ICT) in the public domain, has become an increasingly important vehicle for political communication. It allows people to select and choose the extent of their exposure to political information. Its potential for interactivity between people and sources, and its wealth of information are all thought to facilitate widespread political change. The use of e-governance as a tool has altered the flow of information throughout society and as a result, it has made a lot of impact on the political behaviour of the general public. However, in Nigeria, the accessibility of women to the application of information communication technology is limited compared to their male counterparts. This paper examines how e-governance can address the documented challenges facing Nigerian women such as low income, educational and sociocultural factors, among others, to improve their participation in political issues. The paper, which utilizes secondary sources of gathering information, explores how e-governance can help improve women‟s participation in Nigerian politics beyond being a voter, a cheer-leader or campaigners alone. It submits that, strategies for enhancing women‟s political participation must take into cognizance the use of e-governance for accessing relevant political information that minimizes their disadvantages in the electoral process.